2022
DOI: 10.1002/uog.23730
|View full text |Cite
|
Sign up to set email alerts
|

Second‐trimester contingent screening for small‐for‐gestational‐age neonate

Abstract: Objectives First, to investigate the additive value of second‐trimester placental growth factor (PlGF) for the prediction of a small‐for‐gestational‐age (SGA) neonate. Second, to examine second‐trimester contingent screening strategies. Methods This was a prospective observational study in women with singleton pregnancy undergoing routine ultrasound examination at 19–24 weeks' gestation. We used the competing‐risks model for prediction of SGA. The parameters for the prior model and the likelihoods for estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Therefore, we did not examine the performance of sFlt-1 after 32 weeks. The sFlt-1/PlGF ratio likelihood had a similar structure to the one that was fitted for PlGF in a previous study [14]. Measurement of sFlt-1 did not improve the prediction of SGA (<10th percentile or <3rd percentile), with or without PE, and delivery at <32 weeks' gestation provided by maternal factors alone, at a fixed false positive rate of 10% (Table 3).…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…Therefore, we did not examine the performance of sFlt-1 after 32 weeks. The sFlt-1/PlGF ratio likelihood had a similar structure to the one that was fitted for PlGF in a previous study [14]. Measurement of sFlt-1 did not improve the prediction of SGA (<10th percentile or <3rd percentile), with or without PE, and delivery at <32 weeks' gestation provided by maternal factors alone, at a fixed false positive rate of 10% (Table 3).…”
Section: Resultsmentioning
confidence: 57%
“…We have previously demonstrated that the model is stable and consistent by an internal validation process [7][8][9]12]. Additionally, applying the inferences for the model's parameters in datasets different than the one that had been used to obtain them has shown that our approach is effective when applied in a new case [14]. We acknowledge the need for external validation of our approach.…”
Section: Strengths and Limitationsmentioning
confidence: 79%
See 3 more Smart Citations